Twelve Weeks of Yoga or Nutritional Advice for Centrally Obese Adult Females - Telles, Shirley; Sharma, Sachin K.; Kala, Niranjan; Pal, Sushma; Gupta, Ram K.; Balkrishna, Acharya (Frontiers in Endocrinology, 2018)
Background: Central obesity is associated with a higher risk of disease. Previously yoga reduced the BMI and waist circumference (WC) in persons with obesity. Additional anthropometric measures and indices predict the risk of developing diseases associated with central obesity. Hence the present study aimed to assess the effects of 12 weeks of yoga or nutritional advice on these measures. The secondary aim was to determine the changes in quality of life (QoL) given the importance of psychological factors in obesity. Material and methods: Twenty-six adult females with central obesity in a yoga group (YOG) were compared with 26 adult females in a nutritional advice group (NAG). Yoga was practiced for 75 minutes/day, 3 days/week and included postures, breathing practices and guided relaxation. The NAG had one 45 minutes presentation/week on nutrition. Assessments were at baseline and 12 weeks. Data were analyzed with repeated measures ANOVA and post-hoc comparisions. Age-wise comparisons were with t-tests. Results: At baseline and 12 weeks NAG had higher triglycerides and VLDL than YOG. Other comparisons are within the two groups. After 12 weeks NAG showed a significant decrease in WC, hip circumference (HC), abdominal volume index (AVI), body roundness index (BRI), a significant increase in total cholesterol and LDL cholesterol. YOG had a significant decrease in WC, sagittal abdominal diameter, HC, BMI, WC/HC, a body shape index, conicity index, AVI, BRI, HDL cholesterol and improved QoL. With age-wise analyses, in the 30 to 45 years age range the YOG showed most of the changes mentioned above whereas NAG showed no changes. In contrast for the 46 to 59 years age range most of the changes in the two groups were comparable. Conclusions: Yoga and nutritional advice with a diet plan can reduce anthropometric measures associated with diseases related to central obesity, with more changes in the YOG. This was greater for the 30-45 year age range, where the NAG showed no change; while changes were comparable for the two groups in the 46-59 year age range. Hence yoga may be especially useful for adult females with central obesity between 30-45 years of age. Trial registration: (CTRI/2018/05/014077).